Detection and Confirmation of Quantitative Trait Loci for Soybean Seed Isoflavones. Issue 2 (1st March 2014) - Smallwood, Christopher J.; Nyinyi, Catherine N.; Kopsell, Dean A.; Sams, Carl E.; West, Dennis R.; Chen, Pengyin; Kantartzi, Stella K.; Cregan, Perry B.; Hyten, David L.; Pantalone, Vincent R.
ABSTRACT: Interest in soybean [ Glycine max (L.) Merr.] isoflavones has increased in recent years owing to numerous reported health benefits. Consequently, quantitative trait loci (QTL) detection for marker‐assisted breeding for isoflavones is being examined for genetic gains. This study sought to detect QTL for soybean isoflavones in a population of 274 recombinant inbred lines derived from a cross between 'Essex' and 'Williams 82' that were subdivided and tested by maturity (early, mid, and late). The field tests were conducted in three environments in 2009 (Knoxville, TN; Harrisburg, IL; and Stuttgart, AR). The population was genotyped with 480 polymorphic single nucleotide polymorphism markers. Isoflavones for each replicate were analyzed by near infrared reflectance spectroscopy, whose prediction equation was based on high performance liquid chromatography. Each maturity test, containing 91 or 92 recombinant inbred lines, was analyzed separately for QTL. In total, 21 QTL were detected: 7 for genistein (chromosomes 5, 6, 9, 13, 17, and 19), 5 for daidzein (chromosomes 5, 6, 9, 13, and 19), 3 for glycitein (chromosomes 6, 9, and 20), and 6 for total isoflavone content (chromosomes 5, 6, 9, 13, and 19). Of these 21 QTL, 12 were confirmed or positional confirmations from other studies. Utilization of these QTL could potentially lead to marker‐assisted selection approaches for genetic gains in improving soybean isoflavones.